Breaking ground : empowering women in the construction industry - Arthur-Aidoo, Bernard; Quartey, Princess Naa Kwarkai; Nunoo, Perry Ransgreg; Alex, Adzinku Kwaku (Emerald points., 2024)
The construction industry has historically been male-dominated due to societal expectations and biases, specifically around the physical demands of the job, as well as a lack of role models and mentors. Breaking Ground addresses the scarcity of women in construction and demonstrates how we can overcome these challenges. Exploring the multifaceted relationship between gender and the construction industry, the authors examine the industry's economic, social, and environmental impacts, challenges faced by the workforce and the specific obstacles that contribute to a lesser involvement of women in the field. Outlining strategies to bridge this gap, they further address the empowerment of women within the industry, discussing cultural and environmental factors that shape their professional experiences and the ways in which women's participation and leadership can be increased. Applying these insights on a global scale, the authors conclude by comparing the status of women in the construction industries in Europe, Asia, and Africa, analysing the unique cultural factors affecting their empowerment and mentorship in different regions. Offering a wealth of insights for academic disciplines ranging from gender and economic studies to sociology and sustainability, this seminal work subverts all expectations to encourage and empower women to break ground both literally and figuratively.